Foliage penetration radar detection and characterization of objects under trees - Davis, Mark E. (Mark Edward) 1945- (Raleigh, NC SciTech Publishing, 2011)
The book reviews developments in the following fields: History of battlefield surveillance; foliage penetration SAR collection system; FOPEN SAR image formation; radio frequency interference suppression; FOPEN target detection and characterization; FOPEN SAR design; FOPEN ground moving target indication; and bistatic FOPEN SAR.
Electronic reproduction.
Keywords: Ground penetrating radar; Forest canopies; Aerial observation (Military science); Automatic tracking; Electric interference; Imaging; Noise control; Radar; Radar -- Interference; Radar -- Military applications; Synthetic aperture radar; Tracking radar; Vegetation and climate; Vegetation management; Electronic books; Earth (Planet) -- Surface -- Remote sensing